Use of qSOFA criteria in prediction of poor prognosis in acute pancreatitis - Goktekin, Mehmet Cagri (Derman Medical Publ, 2019)
Aim: In this study,we aimed to investigate the usability of SOFA and qSOFA criteria in predicting the conditions by which the poor prognosis such as hospitalization in the intensive care unit, long length of hospital stay and death was observed for the patients receiving a diagnosis of acute pancreatitis in the emergency department Material and Method: The data of 98 patients with acute pancreatitis diagnosis which was verified by the computerized abdominal tomography in the university hospital emergency department between 2013 and 2018 were used in our study. that was designed as monocenteric retrospective study. The SOFA and qSOFA criteria of the patients were calculated during the application to the emergency department Results: Fifty-three percent (n=52) of the patients were female. Their age averages were 57.5 +/- 8.57/year. Forty-eight (%49.0) patients were detected to have any of the poor prognostic criteria. It was also detected that the qSOFA score of 17 (517.3) patients were 1 and above and the qSOFA score of 81 (582.7) patients was 0 during the application to the emergency department The SOFA (p<0.001) and qSOFA (p=0.004) values were significantly different for the patients having the good prognosis and poor prognosis. When we take the Cut-off as > 0 for the qSOFA criteria, we determined the AUC as 0.641, Sensitivity as %39.58, Specificity as %86, and CI% as 0.538 to 0.735, and p=0.001, respectively. Discussion: The SOFA and qSOFA criteria used in order to predict the organ failure in the sepsis can be a scoring system that will be able to be used in predicting the poor prognosis in acute pancreatitis in the emergency department.
Keywords: Acute Pancreatitis; Emergency Department; Quick SOFA